CVP analysis in the conditions of multi-product production as a tool of operational controlling - N. Babiak; N. Krutous (Вісник аграрної науки Причорномор'я, 2021)
Current conditions for the successful operation of enterprises are characterized by the globalization of the economic sphere, the accelerated pace of scientific and technical progress, and the strengthening of innovative trends. Therefore, any institution, when building its own strategy, first of all strives to provide conditions for long-term and promising activity, which can be achieved only by creating a strong competitive advantage. In particular, a recognized way to win the competition is cost leadership. Therefore, the search for a rational tool for the organization of the cost management system is currently an urgent issue. In addition, the competitiveness of modern enterprises depends on the model of financial flow management. Advantage and leadership in the market goes to organizations that minimize business risks by calculating losses with constant and variable components. CVP analysis is used to calculate the break-even turnover of each type of product. The purpose of the work was to study the application of CPV analysis to solve the problems of multi-product production and cost accounting in order to increase the efficiency of production activities. The article used the method of economic analysis, calculation of break-even points, comparison, modeling. The features of CVP analysis in the conditions of multi-product production are revealed, and the methods of its implementation are compared. The possibilities of applying the results of the analysis when making management decisions in the operational controlling system are determined. The problem of distribution of total fixed undistributed costs for certain types of products by various methods, as well as determination of the break-even level of production and sale of certain types of products on the basis of weighted average marginal profit, was investigated. The impact on profit of a change in the level of fixed costs and specific variable costs with the help of operating leverage as part of an operational analysis at a manufacturing enterprise was studied